IMPLEMENTASI AGROEKOLOGI PADA SISTEM USAHA TANI DI PONDOK PESANTREN ANWARUSH SHOLIHIN PURWOKERTO - Ahmad Fauzi; Ahadiyat Yugi R; Kuntarto Kuntarto; Riza Chamadi (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2023)
Islamic boarding school students are one of the human resources that have a strategic role in national development. In addition to studying religion, students are also expected to have adequate skills and knowledge in environmentally friendly agriculture. Many Islamic boarding schools carry out productive businesses in the agricultural sector as a source of income and learning facilities for students, one of which is the. This community service activity aims to improve the understanding and skills of students of Anwarush Sholihin Islamic Boarding School, Purwokerto Selatan, in applying the concept of agroecology in farming and environmental management. The activities included outreach, counseling, procurement of agricultural facilities, initiation of maggot cultivation, banana planting, fertilizer-making training, beekeeping training, and program evaluation. The results showed an increase of students' understanding and skills in implementing agroecology-based agriculture. In addition, the optimization of unused land around the Islamic boarding school has been converted to a banana plantation integrated with goat, magot, and beekeeping farms.